Carbon dioxide adsorption on mesoporous magnesium carbonate. (February 2019) - Vall, Maria; Hultberg, Jonas; Strømme, Maria; Cheung, Ocean
Abstract: Mesoporous magnesium carbonate (MMC) was synthesized and tested for its ability to separate CO2 from N2 . The pure gas CO2 uptake of MMC was around 1.5 mmol/g at 101 kPa, 0 °C. The N2 uptake under the same conditions was less than 0.1 mmol/g. Al(NO3 )3, Al2 O3, K2 CO3 and KNO3 were introduced into the porous structure of MMC as additives. All of the additives tested increased the CO2 uptake of MMC and increased its selectivity towards CO2 . The incorporation of 5 wt.% K2 CO3 increased the CO2 uptake of MMC up to over 3.2 mmol/g. The ideally adsorbed solution theory was used to calculate the CO2 selectivity of MMC and MMC with additives for a hypothetical gas mixture that contained 15% CO2 : 85% N2 . The CO2 selectivity at 101 kPa (0 °C) was around 60. MMC with 5 wt.% K2 CO3 had a CO2 selectivity of over 150 under the same conditions. Vacuum swing cyclic CO2 adsorption/desorption showed that the CO2 uptake on MMC with 5 wt.% K2 CO3 decreased after each cycle. Heat regeneration (up to 250 °C, for 10 minutes) could recover most of the lost CO2 capacity after each cycle. Heat regeneration indicatively improved the cyclic performance of this adsorbent. MMC with 5 wt.% K2 CO3 was the best performing adsorbent in this study and can potentially be further developed into a good CO2 adsorbent for temperature swing adsorption (TSA) processes.